Enhancing melt foam stability, form-filling process, and pore structure evolution of shaped aluminum foam - Tan Wang; Xiaoqing Zuo; Jianhong Yi; Yun Zhou; Xiaoxu Luo; Shibing Guo; Wenkai Song (Journal of Materials Research and Technology)
This study explores the stability of Al–Si–Ca–Mg-Sc melt foams and investigates the melt foam filling process and the dynamic evolution of pore structures in the fabrication of foam aluminum profiles using the melt transfer foaming technique. The results show that Al–Si–Ca–Mg-Sc melt foam maintains high porosity and a stable pore structure even after 30 min of foaming, without any signs of boundary rupture or destabilization. This stability is attributed to the increased viscosity from finely dispersed second-phase particles, which hinder the growth, coalescence, and drainage of the melt foam. Regarding melt foam filling, enhanced filling capability is achieved by elevating the foaming temperature, extending the foaming time, and increasing the TiH2 addition. The melt foam exhibits a smooth flow from the lower part of the mold to the corners, completing the filling process with well-defined edges in the profile. During lateral movement for filling, a gradual increase in porosity, a decrease in pore number, and a slow enlargement of pore size and standard deviation along the lateral (x-axis) are observed. This is due to the slower liquid phase flow compared to the gas phase, resulting in bubble coalescence. After filling is complete, this phenomenon improves, contributing to a slow and stable evolution of the pore structure.Under optimized conditions of 1.4 wt% TiH2 addition at 600°Cfor 9 min of foaming with Al–Si–Ca–Mg-Sc alloy melting, we successfully fabricated foam aluminum profiles with complete filling, a porosity of 81.5%, an average pore size of 2–3 mm, and a uniform pore structure.